Surface-tailored nanodiamonds as excellent metal-free catalysts for organic oxidation. (July 2016) - Duan, Xiaoguang; Ao, Zhimin; Li, Degang; Sun, Hongqi; Zhou, Li; Suvorova, Alexandra; Saunders, Martin; Wang, Guoxiu; Wang, Shaobin
Abstract: Metal-free catalysis has demonstrated competitive performance in energy conversion and chemical synthesis, yet scenarios in environmental catalysis are scant. The application of carbocatalysis for preventing secondary contamination by heavy/noble metals is envisaged as benign remediation. In this paper, we report a facile alteration of the surface chemistry of nanodiamond, a biocompatible nanocarbon, for application to environmental catalysis. The modulation is able to improve the redox capability of potassium ferricyanide (III) and to enhance the performance of the nanodiamond for activating peroxymonosulfate (PMS) to produce sulfate and hydroxyl radicals for catalytic oxidation. Cyclic voltammetry analysis, electron paramagnetic resonance (EPR) spectra, classical quenching tests, and density functional theory (DFT) calculations are integrated for a mechanistic study. This paper discusses highly efficient green materials for environmental catalysis and offers new insights into the heterogeneous carbocatalysis.